Occurrence and concentrations of phthalates, alternative plasticizers and other additives in food samples from the German market - Andriy Kuklya; Elisabeth Koch; Ezgi Eyluel Bankoglu; Oliver Kappenstein; Irmela Sarvan; Sara Perestrelo; Sebastian Zellmer; Thomas Tietz; Oliver Lindtner; Andreas Luch; Alexander Roloff; Torsten Bruhn (Food Chemistry, 2026)

Genetic dissection of grain yield and correlated proxy traits under suboptimal conditions - Yan-Cheng Lin; Claude Urbany; Antonina Shlykova; Armin C. Hölker; Milena Ouzunova; Thomas Presterl; Torsten Pook; Manfred Mayer; Sebastian Urzinger; Chris-Carolin Schön (Theoretical and Applied Genetics, 2026)
Key message This eight-founder MAGIC population represents a powerful resource for dissecting complex traits in maize, assessing the utility of drought proxy traits, and optimizing low-coverage whole-genome sequencing approaches. Abstract Securing sustainable crop production requires the genetic improvement of abiotic stress tolerance. Due to the broad range of environmental factors causing abiotic stress and complex genotype-by-environment interactions, it is crucial to understand the genetic basis of crop yield under suboptimal conditions. Here, we developed a dent maize Multi-parent Advanced Generation Inter-Cross (MAGIC) population comprising 388 doubled-haploid (DH) lines. The population was derived from eight founders with varying stress tolerance, selected from a dent diversity panel evaluated for yield performance across a wide range of European environments. The MAGIC DH lines were genotyped via whole-genome sequencing (~ 5× coverage) and evaluated in seven testcross and 14 line per se trials, for grain yield, leaf senescence, leaf rolling, anthesis-silking interval, and six additional agronomic traits. Genetic dissection identified 22 grain yield QTL, explaining 45% of the genetic variance. Under heat and drought stress, testcross grain yield correlated significantly with leaf senescence and leaf rolling measured in line per se trials. Bivariate multi-trait analysis showed that alleles for delayed senescence and reduced rolling at detected QTL generally exhibited positive effects on grain yield, suggesting that accumulating these favorable alleles could enhance yield performance. Incorporating these proxies into multi-trait genomic prediction models improved yield prediction accuracy, although gains were constrained by modest trait correlations. Given the comprehensive data, we also provide recommendations for optimizing sequencing depth and QTL mapping strategies in experimental maize populations.

Flow reactor oxidation study of oxymethylene ether (OME1–3): Insights from molecular-beam mass spectrometry and kinetic modeling at elevated pressure - Thomas Bierkandt; Trupti Kathrotia; Sascha Jacobs; Nina Gaiser; Jasmin Schmittner; Fabienne Werner; Joachim Schmid; Torsten Methling; Patrick Oßwald; Markus Köhler (Fuel, 2026)

Towards Key Principles of Host‐Associated Microbiome Assembly - Gui Araujo; Torsten Thomas; José M. Montoya; Nicole S. Webster; Miguel Lurgi (Ecology Letters, 2026)
Symbiotic relationships between microbes and hosts frequently involve the assembly of complex microbial communities. Community‐level patterns influence life‐history traits, ecological trajectories of partners, and are often critical for host health. These patterns are driven by mechanisms acting at the individual level, including microbial dispersal, host selection, and microbe–resource interactions. Critically, we still lack a clear picture of how these mechanisms interact to shape microbiome assembly. We present a model that describes how distinct community structures arise from those underlying mechanisms. To illustrate the approach, we simulate microbiome data from marine sponges, thereby bridging mechanistic models and empirical patterns. We further apply the model to human data to explore its relevance across systems, proposing that a small set of general mechanisms may govern diverse patterns of diversity and abundance. Our findings advance ecological theory by linking individual‐level processes to community‐scale patterns, illuminating key drivers of microbiome assembly.

Hierarchical constitutive modeling of structured clays: Bridging element tests and mechanized tunneling simulations - Thomas Barciaga; Mahdi Taiebat; Maria Datcheva; Torsten Wichtmann (Computers and Geotechnics, 2026)

High thermotolerance to extreme marine heatwaves for four New Caledonian sponges - Barbara J. Graham; Simon K. Davy; Lisa Woods; Torsten Thomas; Riccardo Rodolfo-Metalpa; James J. Bell (Marine Pollution Bulletin, 2026)

Multi-millennial reconstruction of fire return intervals from a fynbos – Afrotemperate forest ecotone in the Cape Floristic Region, South Africa: Paleoecological implications for present-day management - Stella G. Mosher; Mitchell J. Power; Lynne J. Quick; Brian M. Chase; Torsten Haberzettl; Thomas Kasper; Simon C. Brewer; David R. Braun; J. Tyler Faith (Global and Planetary Change, 2026)

Positive inotropic effects of serotonin in atrial EHT: further proof for an atrial phenotype? - Muhammed Sönmez; Margaret Nandudu; Paul Brunnbauer; Carl Schulz; Birgit Klampe; Thomas Schulze; Arne Hansen; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) cultured in the presence of retinoic acid were proposed as a model for human atrium. Since in the human heart positive inotropic effects of serotonin (5-HT) are restricted to the atrium, we investigated whether the presence of 5-HT responses may distinguish between hiPSC-atrial and ventricular CM. Nonfiltered retinoic acid (1 µM) was used to induce an atrial phenotype (hiPSC-aCM) in two different hiPSC lines. Untreated hiPSC-CM were used as controls (ventricular). We measured 5-HT4 receptor ( HTR4 ) expression and 5-HT effects on Ca 2+ currents (I Ca ), force, and action potential in engineered heart tissue (EHT). HTR4 transcript abundance was five times higher in atrial EHT. 5-HT (100 µM) increased I Ca from 5.3 ± 0.8 to 8.1 ± 1.1 pA/pF, prolonged APD 20 from 8.1 ± 1.2 to 12.0 ± 1.2 ms, and shortened APD 90 from 142.3 ± 11.3 to 117.0 ± 6.6 ms in hiPSC-aCM, but not in hiPSC-vCM. 5-HT increased force in atrial EHTs from 0.06 ± 0.01 to 0.10 ± 0.01 mN but not in vEHT. Spontaneous beating rate per minute was increased by 5-HT in aEHT from 151.3 ± 7.5 to 173.7 ± 4.1 and in vEHT from 43.1 ± 4.2 to. 61.3 ± 3.4. Both EHTs contain functional 5-HT receptors, but 5-HT increases I Ca and force only in aEHT, similar to the human heart. In vEHT, 5-HT’s positive chronotropic effect in the absence of I Ca stimulation and inotropic response suggests activation of funny channels. Our findings demonstrate that aEHT shares the typical atrial-selective regulation of I Ca and force by 5-HT, thus making aEHT a promising model to study 5-HT 4 receptors in the human heart.

Sex differences in human atrial electrophysiology: the dark side of the moon? Will engineered heart tissue help to bring light into the darkness? - Djemail Ismaili; Junsoo Im; Renate B. Schnabel; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Sex-related differences in cardiac electrophysiology are well established in the ventricle and have reached textbook level. In contrast, our understanding of sex effects in the human atrium remains limited, despite clear clinical observations such as the lower incidence of atrial fibrillation (AF) in women. In this review, we summarize sex differences and discuss potential reasons for the imbalance in knowledge, including the lack of ECG markers for atrial repolarization, the minimal contribution of I Ks in atrial tissue, and possible sex differences in inward rectifier currents. We also address the role of aging and hormonal changes, the complexity of studying the perimenopausal transition, and the current limitations of available models. Finally, we highlight the potential of engineered heart tissues to detect genetically encoded differences and to dissect genomic versus non-genomic hormone effects.

Heat but Not Cold Tolerance Is Phylogenetically Constrained in Greenlandic Terrestrial Arthropods Under Future Global Warming - Jonas Bruhn Wesseltoft; Nadieh de Jonge; Michael Møller Hansen; Toke Thomas Høye; Michael Ørsted; Torsten Nygaard Kristensen (Global Change Biology, 2026)
The Arctic is currently warming at up to four times the global average. Likewise, climate variability within and across seasons is predicted to markedly increase in the future. This may challenge organisms in these pristine environments, making it critically important to understand their thermal biology and evolutionary potential. For Arctic ectotherms in particular, thermal tolerance limits and responses to climate change are mostly unknown. Knowledge on this is urgently needed to enable prediction of climate change impacts on future distributions of biodiversity in these rapidly changing environments. Here, we provide data on upper and lower thermal limits of 93 Greenlandic species of insects, arachnids, and collembolans caught and tested in the field and identified using barcode sequencing. This represents ~8% of described terrestrial Greenlandic arthropod species. We found pronounced differences in heat and cold tolerance among species and a strong phylogenetic signal for both heat tolerance and thermal scope (difference between upper and lower thermal limits). We argue that this indicates a limited capacity for coping with increasing and more variable future temperatures through evolutionary adaptation. Further, we modelled future increases in microhabitat temperatures in our sampling area. We found that > 25% of the investigated species may periodically experience stressful high temperatures in the future. These results suggest that climate change will likely result in substantial changes in distributions and abundances of terrestrial arthropods in Southern Greenland.

Extraordinary occlusion of caniniforms in the Eocene Masillabune martini from Messel - Wighart V. Koenigswald; Thomas Lehmann; Torsten Wappler (Palaeobiodiversity and Palaeoenvironments, 2025)
The skeleton of the small artiodactyl Masillabune martini Tobien 1980 is a typical example of the mammalian skeletons excavated by private collectors in the famous Messel-Fossillagerstätte in 1970 s, long before the locality became a World Heritage Site. Although the skeleton was found during a private excavation by Thomas Martin, the well-preserved skeleton eventually found its way to a public museum, the Hessisches Landesmuseum in Darmstadt (HLMD). Tobien provided the scientific description of the specimen and erected the skeleton as the type for the species Masillabune martini in honour of the finder. Masillabune martini is a small choeropotamid artiodactyl and differs from many mammals in the occlusion pattern of its caniniform teeth. In contrast to the normal “lower canines mesial to upper canines” pattern, the lower canine of M. martini is reduced and incisiform, whereas the first lower premolar is caniniform and acts as an antagonist to the upper canine, albeit located distally. This occlusal pattern is not an isolated pathological modification, because it occurs in a number of independent mammalian groups as the “canine/premolar functional unit”. The convergent development of this specific occlusal pattern of caniniforms characterises a morphological cluster including Merycoidodontidae and Protoceratidae.

Evaluating climatic and anthropogenic drivers of fire activity over four millennia at Eilandvlei, southern Cape coast, South Africa - Stella G. Mosher; Mitchell J. Power; Brian M. Chase; Lynne J. Quick; Torsten Haberzettl; Thomas Kasper; David R. Braun; J. Tyler Faith (Quaternary Science Reviews, 2025)

Exploring the impact of siloxane networks on the thermal behavior of P/N-enriched flame-retardant finishes for cotton fabric - Raphael Otto; Wael Ali; Eui-young Shin; Alexander M. Preußner; Hung M. Phan; Torsten Textor; Jochen S. Gutmann; Thomas Mayer-Gall (Chemical Engineering Journal, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Optimizing Ulva-Phaeobacter co-culture: A two-phase light intensity approach for integrated multi-trophic aquaculture applications - Gonzalo Del Olmo; Patricia Ruiz; Jadranka Nappi; Torsten Thomas; Suhelen Egan; Javier Cremades; José Pintado (Journal of Applied Phycology, 2025)
Incorporating macroalgae like Ulva species into integrated multi-trophic aquaculture (IMTA) enhances sustainability by filtering effluents and provide epiphytic bacteria, that can contribute to disease prevention. Colonizing Ulva ohnoi with Phaeobacter sp. 4UAC3 is promising for disease control in IMTA systems, but high light intensity impacts Phaeobacter ’s persistence on Ulva . This study investigated the effect of different light intensities and regimes on the ability of Phaeobacter sp. 4UAC3·to colonize U. ohnoi . Experiments assessed algal growth, water physicochemistry, and microbial profiles using culture techniques and 16S rRNA gene sequencing. Light intensities of 143, 75, 45, and 0 μmol photons m −2 s −1 were tested on U. ohnoi and non-living surfaces inoculated with Phaeobacter sp. 4UAC3. Results showed that Phaeobacter sp. 4UAC3 colonization on U. ohnoi decreased in the light but remained stable in the dark. On non-living surfaces, Phaeobacter persisted regardless of light intensity, suggesting light does not directly affect the bacterium. However, light had an impact on microbial community structure on U. ohnoi , with genera including Glaciecola , Maribacter and Roseobacter significantly enriched under higher light conditions. This suggests the disappearance of Phaeobacter sp. 4UAC3 is in part a result of competition with specific bacteria. Additionally, the chemical microenvironment of the algae influenced by light could be important in Phaeobacter disappearance, although further research is required. Finally, optimal co-culture involved alternating dark and low-light (45 μmol photons·m −2 s −1 ) phases, enhancing Phaeobacter sp. 4UAC3 maintenance and optimal algal growth. This knowledge will optimize a fish-algae IMTA-RAS using Ulva colonized with Phaeobacter .

Improving geothermal doublet efficiency in multiple sandstone horizons in Hannover/Germany - Jonas Suilmann; Torsten Tischner; Thomas Graf (Grundwasser, 2025)
In Hannover, Germany, a deep borehole was drilled to explore the use of geothermal energy for the heat supply of office buildings. The targets are multiple subdivided sandstone horizons of the Wealden formation (Lower Cretaceous) at a depth of 1200–1300 m and a temperature of around 70 °C. The technical feasibility of the doublet operation is assessed by numerically investigating the effects of well spacing, injection/production rate and injection temperature using a 3D model. In particular, the production temperature drop is investigated to optimize well spacing and doublet lifetime. The effect of uncertain sandstone permeability and surrounding rock thermal conductivity on doublet lifetime is also investigated. The results indicate that a doublet well spacing of 500 m can sustain heat production with a thermal power output of 0.5 to 2 MW over a lifetime of at least 30 years, demonstrating the general feasibility of geothermal heat production from multiple sandstone horizons.

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

The biodiversity of the Eocene Messel Pit - Krister T. Smith; Margaret Collinson; Annelise Folie; Jörg Habersetzer; Florian Hennicke; Erika Kothe; Thomas Lehmann; Olaf K. Lenz; Gerald Mayr; Norbert Micklich; Renate Rabenstein; Rachel Racicot; et al. (Palaeobiodiversity and Palaeoenvironments, 2024)
The Messel Pit is a Konservat-Lagerstätte in Germany, representing the deposits of a latest early to earliest middle Eocene maar lake, and one of the first palaeontological sites to be included on the list of UNESCO World Heritage Sites. One aspect of Messel that makes it so extraordinary is that its sediments are rich in different fossilised organisms – microfossils, plants, fungi, invertebrate animals and vertebrates – that are rarely preserved together. We present an updated list of all taxa, named or not, that have been documented at Messel, comprising 1409 taxa, which represent a smaller but inexactly known number of biological species. The taxonomic list of Labandeira and Dunne (2014) contains serious deficiencies and should not be used uncritically. Furthermore, we compiled specimen lists of all Messel amphibians, reptiles and mammals known to us. In all, our analyses incorporate data from 32 public collections and some 20 private collections. We apply modern biodiversity-theoretic techniques to ascertain how species richness tracks sampling, to estimate what is the minimum asymptotic species richness, and to project how long it will take to sample a given proportion of that minimum richness. Plant and insect diversity is currently less well investigated than vertebrate diversity. Completeness of sampling in aquatic and semiaquatic, followed by volant, vertebrates is higher than in terrestrial vertebrates. Current excavation rates are one-half to two-thirds lower than in the recent past, leading to much higher estimates of the future excavation effort required to sample species richness more completely, should these rates be maintained. Species richness at Messel, which represents a lake within a paratropical forest near the end of the Early Eocene Climate Optimum, was generally higher than in comparable parts of Central Europe today but lower than in present-day Neotropical biotopes. There is no evidence that the Eocene Messel ecosystem was a “tropical rainforest.”

Deep-time maar lakes and other volcanogenic lakes as Fossil-Lagerstätten – An overview - Dieter Uhl; Michael Wuttke; Manuela Aiglstorfer; Carole T. Gee; Federica Grandi; Olaf Höltke; Thomas M. Kaiser; Uwe Kaulfuss; Daphne Lee; Thomas Lehmann; Oriol Oms; Markus J. Poschmann; et al. (Palaeobiodiversity and Palaeoenvironments, 2024)
Deep-time (=pre-Quaternary) maar lakes and certain other, hydrologically deep volcanogenic lakes, are often excellent Konservat-Lagerstätten representing unique windows into past biota and ecosystems. Many deposits from such lakes contain animal and plant remains in extraordinary preservation, often with soft tissues or fine morphological and anatomical details preserved. Such Lagerstätten have the potential to provide in-depth information on a variety of organisms, which is important for understanding their biology and ecology, their evolution and palaeobiogeography, but also for elucidating entire ecosystems with their numerous biotic and abiotic interactions. The formation of such Lagerstätten is intimately linked to volcanic processes, amongst which phreatomagmatic explosions that formed maar-diatreme volcanoes are probably the most important, but also other volcanic processes can lead to the formation of deep volcanogenic lakes (e.g. in certain calderas). Maar lakes and other volcanogenic Konservat-Lagerstätten occur in a large number of volcanically active regions worldwide, although older deposits are often difficult to access as they are more likely to be eroded or covered by younger deposits. The accessibility of many of the better-known localities is often connected to the mining of natural resources, ranging from diamonds, to volcanic rocks such as basalts to the lacustrine sediments that may have filled volcanic craters, including diatomites and ‘oil-shales’. Most or even all of the maar and other volcanogenic lakes presented here in greater detail, can be considered as important geoheritage sites. Although currently some of these deposits have at least some kind of legal protection as monuments of natural heritage, others remain in danger of being exploited commercially for natural resources and hence, ultimately destroyed. Moreover, many scientific questions related to these ancient lakes and their biota covered here in more detail, as well as those related to lakes only briefly mentioned in passing, have not been posed, let alone answered. This makes maar lakes and other volcanogenic lakes important resources for present-day and future research. The present contribution should be seen as a global call to scientists to find further localities that represent similar volcanogenic lacustrine settings, as they may be the source of vital and surprising new information about the plants, animals, and environments of the past. Examples of pre-Quaternary maar and other volcanogenic lakes that are presented here in greater detail include the following localities: Paleocene : Menat (France); Eocene : Messel, Eckfeld (Germany), Mahenge (Tanzania); Oligocene : Enspel, Rott, Hammerunterwiesenthal, Baruth, Kleinsaubernitz (Germany); Miocene : Foulden Maar, Hindon Maar Complex (New Zealand), Randeck Maar, Hirnkopf-Maar, Höwenegg, Öhningen (Germany); Pliocene : Ruppach-Goldhausen (Germany), Camp dels Ninots (Spain).

Causes and consequences of natural and anthropogenically induced late Holocene hydrological variations on the largest freshwater system in the Lesser Caucasus (Lake Sevan, Armenia) - Torsten Haberzettl; Marie-Luise Adolph; Taron Grigoryan; Hayk Hovakimyan; Thomas Kasper; Norbert Nowaczyk; Christian Zeeden; Lilit Sahakyan (Quaternary Science Reviews, 2024)

Chemical imitation of yeast fermentation by the drosophilid-pollinated deceptive trap-flower Aristolochia baetica (Aristolochiaceae) - Thomas Rupp; Birgit Oelschlägel; Regina Berjano; Hafez Mahfoud; Daniele Buono; Torsten Wenke; Katharina Rabitsch; Gerhard Bächli; Vesna Stanojlovic; Chiara Cabrele; Wujian Xiong; Markus Knaden; et al. (Phytochemistry, 2024)

Marine heatwave‐driven mass mortality and microbial community reorganisation in an ecologically important temperate sponge - James J. Bell; Valerio Micaroni; Francesca Strano; Ken G. Ryan; Katherine Mitchell; Paul Mitchell; Shaun Wilkinson; Torsten Thomas; Ramadian Bachtiar; Robert O. Smith (Global Change Biology, 2024)
Marine heatwaves (MHWs) are increasing in frequency, duration and intensity, disrupting global marine ecosystems. While most reported impacts have been in tropical areas, New Zealand experienced its strongest and longest MHW in 2022, profoundly affecting marine sponges. Sponges are vital to rocky benthic marine communities, with their abundance influencing ecosystem functioning. This study examines the impact of this MHW on the photosynthetic sponge Cymbastella lamellata in Fiordland, New Zealand. We describe the extent, physiological responses, mortality, microbial community changes and ecological impact of this MHW on C. lamellata . The Fiordland MHW reached a maximum temperature of 4.4°C above average, lasting for 259 days. Bleaching occurred in >90% of the C. lamellata Fiordland population. The population size exceeded 66 million from 5 to 25 m, making this the largest bleaching event of its kind ever recorded. We identified the photosynthetic symbiont as a diatom, and bleached sponges had reduced photosynthetic efficiency. Post‐MHW surveys in 2023 found that over 50% of sponges at sampling sites had died but that the remaining sponges had mostly recovered from earlier bleaching. Using a simulated MHW experiment, we found that temperature stress was a driver of necrosis rather than bleaching, despite necrosis only rarely being observed in the field ( C. lamellata are key contributors of dissolved organic carbon to the water column, with their loss likely impacting ecosystem function. We demonstrate the potential for MHWs to disrupt key marine phyla in temperate regions, highlighting how susceptible temperate sponges globally might be to MHWs.

Effect of marine heatwaves and warming on kelp microbiota influence trophic interactions - Louise C. Castro; Adriana Vergés; Sandra C. Straub; Alexandra H. Campbell; Melinda A. Coleman; Thomas Wernberg; Peter Steinberg; Torsten Thomas; Symon Dworjanyn; Paulina Cetina‐Heredia; Moninya Roughan; Ezequiel M. Marzinelli (Molecular Ecology, 2024)
The range‐expansion of tropical herbivores due to ocean warming can profoundly alter temperate reef communities by overgrazing the seaweed forests that underpin them. Such ecological interactions may be mediated by changes to seaweed‐associated microbiota in response to warming, but empirical evidence demonstrating this is rare. We experimentally simulated ocean warming and marine heatwaves (MHWs) to quantify effects on two dominant temperate seaweed species and their microbiota, as well as grazing by a tropical herbivore. The kelp Ecklonia radiata 's microbiota in sustained warming and MHW treatments was enriched with microorganisms associated with seaweed disease and tissue degradation. In contrast, the fucoid Sargassum linearifolium 's microbiota was unaffected by temperature. Consumption by the tropical sea‐urchin Tripneustes gratilla was greater on Ecklonia where the microbiota had been altered by higher temperatures, while Sargassum 's consumption was unaffected. Elemental traits (carbon, nitrogen), chemical defences (phenolics) and tissue bleaching of both seaweeds were generally unaffected by temperature. Effects of warming and MHWs on seaweed holobionts (host plus its microbiota) are likely species‐specific. The effect of increased temperature on Ecklonia 's microbiota and subsequent increased consumption suggest that changes to kelp microbiota may underpin kelp‐herbivore interactions, providing novel insights into potential mechanisms driving change in species' interactions in warming oceans.

Not all parents are the same: Diverse strategies of symbiont transmission in seaweeds - Syukur Syukur; Joanna Richmond; Marwan E. Majzoub; Jadranka Nappi; Suhelen Egan; Torsten Thomas (Environmental Microbiology, 2024)
Different marine seaweed species have been shown to harbour specific bacterial communities, however, the extent to which vertical symbiont transmission from parents to offspring contributes to host‐specificity is unclear. Here we use fluorescence and electron microscopy as well as 16S rRNA gene‐based community analysis to investigate symbiont transmission in members of the three major seaweed groups (green Chlorophyta , red Rhodophyta and brown Phaeophyceae ). We found seaweeds employ diverse strategies to transfer symbionts to their progeny. For instance, the green Ulva australis does not appear to have the capacity for vertical transmission. In contrast, the brown Phyllospora comosa adopts a non‐selective vertical transmission. The red Delisea pulchra demonstrates weak selectivity in symbiont transmission, while the brown Hormosira banksii exhibits a strongly selective symbiont transfer. Mucilage on the gametes appears to facilitate vertical transmission and transferred bacteria have predicted properties that could support early development of the seaweeds. Previous meta‐analysis has indicated that vertical transmission is rare in aquatic compared to terrestrial environments, however, our results contribute to the growing evidence that this might not be the case and that instead vertical transmission with various degrees of symbiont selection occurs in the ecologically important group of seaweeds.

The impact of interspecific competition on the genomic evolution of Phaeobacter inhibens and Pseudoalteromonas tunicata during biofilm growth - Weizhi Song; Shan Zhang; Marwan E. Majzoub; Suhelen Egan; Staffan Kjelleberg; Torsten Thomas (Environmental Microbiology, 2024)
Interspecific interactions in biofilms have been shown to cause the emergence of community‐level properties. To understand the impact of interspecific competition on evolution, we deep‐sequenced the dispersal population of mono‐ and co‐culture biofilms of two antagonistic marine bacteria ( Phaeobacter inhibens 2.10 and Pseudoalteromononas tunicata D2). Enhanced phenotypic and genomic diversification was observed in the P. tunicata D2 populations under both mono‐ and co‐culture biofilms in comparison to P. inhibens 2.10. The genetic variation was exclusively due to single nucleotide variants and small deletions, and showed high variability between replicates, indicating their random emergence. Interspecific competition exerted an apparent strong positive selection on a subset of P. inhibens 2.10 genes (e.g., luxR , cobC , argH , and sinR ) that could facilitate competition, while the P. tunicata D2 population was genetically constrained under competition conditions. In the absence of interspecific competition, the P. tunicata D2 replicate populations displayed high levels of mutations affecting the same genes involved in cell motility and biofilm formation. Our results show that interspecific biofilm competition has a complex impact on genomic diversification, which likely depends on the nature of the competing strains and their ability to generate genetic variants due to their genomic constraints.

Modulating cardiac physiology in engineered heart tissue with the bidirectional optogenetic tool BiPOLES - Barbora Schwarzová; Tim Stüdemann; Muhammed Sönmez; Judith Rössinger; Bangfen Pan; Thomas Eschenhagen; Justus Stenzig; J. Simon Wiegert; Torsten Christ; Florian Weinberger (Pflügers Archiv - European Journal of Physiology, 2023)
Optogenetic actuators are rapidly advancing tools used to control physiology in excitable cells, such as neurons and cardiomyocytes. In neuroscience, these tools have been used to either excite or inhibit neuronal activity. Cell type–targeted actuators have allowed to study the function of distinct cell populations. Whereas the first described cation channelrhodopsins allowed to excite specific neuronal cell populations, anion channelrhodopsins were used to inhibit neuronal activity. To allow for simultaneous excitation and inhibition, opsin combinations with low spectral overlap were introduced. BiPOLES (Bidirectional Pair of Opsins for Light-induced Excitation and Silencing) is a bidirectional optogenetic tool consisting of the anion channel Guillardia theta anion-conducting channelrhodopsin 2 (GtACR2 with a blue excitation spectrum and the red-shifted cation channel Chrimson. Here, we studied the effects of BiPOLES activation in cardiomyocytes. For this, we knocked in BiPOLES into the adeno-associated virus integration site 1 (AAVS1) locus of human-induced pluripotent stem cells (hiPSC), subjected these to cardiac differentiation, and generated BiPOLES expressing engineered heart tissue (EHT) for physiological characterization. Continuous light application activating either GtACR2 or Chrimson resulted in cardiomyocyte depolarization and thus stopped EHT contractility. In contrast, short light pulses, with red as well as with blue light, triggered action potentials (AP) up to a rate of 240 bpm. In summary, we demonstrate that cation, as well as anion channelrhodopsins, can be used to activate stem cell–derived cardiomyocytes with pulsed photostimulation but also to silence cardiac contractility with prolonged photostimulation.

Differential priority effects impact taxonomy and functionality of host‐associated microbiomes - Jadranka Nappi; Priscila Goncalves; Tahsin Khan; Marwan E. Majzoub; Anna Sophia Grobler; Ezequiel M. Marzinelli; Torsten Thomas; Suhelen Egan (Molecular Ecology, 2023)
Most multicellular eukaryotes host complex communities of microorganisms, but the factors that govern their assembly are poorly understood. The settlement of specific microorganisms may have a lasting impact on community composition, a phenomenon known as the priority effect. Priority effects of individual bacterial strains on a host's microbiome are, however, rarely studied and their impact on microbiome functionality remains unknown. We experimentally tested the effect of two bacterial strains ( Pseudoalteromonas tunicata D2 and Pseudovibrio sp. D323) on the assembly and succession of the microbial communities associated with the green macroalga Ulva australis . Using 16S rRNA gene sequencing and qPCR, we found that both strains exert a priority effect, with strain D2 causing initially strong but temporary taxonomic changes and strain D323 causing weaker but consistent changes. Consistent changes were predominately facilitatory and included taxa that may benefit the algal host. Metagenome analyses revealed that the strains elicited both shared (e.g., depletion of type III secretion system genes) and unique (e.g., enrichment of antibiotic resistance genes) effects on the predicted microbiome functionality. These findings indicate strong idiosyncratic effects of colonizing bacteria on the structure and function of host‐associated microbial communities. Understanding the idiosyncrasies in priority effects is key for the development of novel probiotics to improve host condition.

Advancing co-production for transformative change by synthesizing guidance from case studies on the sustainable management and governance of natural resources - Fernanda A. van Maurik Matuk; Bas Verschuuren; Piero Morseletto; Torsten Krause; David Ludwig; Steven J. Cooke; Moacir Haverroth; Marieke Meesters; Thomas J.M. Mattijssen; Sabine Keßler; Tomaz R. Lanza; Esther Milberg; et al. (Environmental Science & Policy, 2023)

Manipulating the Ulva holobiont: Co-culturing Ulva ohnoi with Phaeobacter bacteria as a strategy for disease control in fish-macroalgae IMTA-RAS aquaculture - José Pintado; Gonzalo Del Olmo; Thomas Guinebert; Patricia Ruiz; Jadranka Nappi; Torsten Thomas; Suhelen Egan; Ingrid Masaló; Javier Cremades (Journal of Applied Phycology, 2023)
The green alga Ulva ohnoi M. Hiraoka & S. Shimada is an effective biofiltration agent of fish effluents in Integrated Multi-Trophic Aquaculture Recirculation Systems (IMTA-RAS), due to its high growth rate and high nutrient (N and P) removal in temperate conditions. Moreover, Ulva species provide an important niche for biofilm-forming bacteria, including strains of Phaeobacter that possess antagonistic activity against pathogenic Vibrio species, and have been shown to reduce the mortality of fish in aquaculture settings. This research aimed to examine the potential of using U. ohnoi colonised with Phaeobacter sp. 4UAC3, previously isolated from natural populations of Ulva australis , as a strategy to prevent vibriosis in IMTA-RAS. The results showed that Phaeobacter sp. 4UAC3 was able to colonise and be maintained on U. ohnoi during a re-inoculation scale-up process from multi-well plates (10 mL) to flasks (4 L) and finally to tanks (40 L). Phaeobacter sp. 4UAC3 rapidly colonised the surface of the Ulva but it did not significantly modify the rest of the bacterial communities present in U. ohnoi surface in terms of diversity and composition. Infection assays using fish larvae ( Scophthalmus maximus ) with V. anguillarum in a model IMTA-RAS showed that Phaeobacter –colonized U. ohnoi promoted the reduction of mortality in the infected larvae, however this trend was not statistically supported. These results suggested that U. ohnoi can be experimentally colonised with Phaeobacter sp. 4UAC3 and has potential to be used in IMTA-RAS as an alternative to traditional disease control methods.

Identification, classification, and functional characterization of novel sponge-associated acidimicrobiial species - Viet Hung Nguyen; Bernd Wemheuer; Weizhi Song; Holly Bennett; Nicole Webster; Torsten Thomas (Systematic and Applied Microbiology, 2023)

Joint inversion of groundwater flow, heat, and solute state variables: a multipurpose approach for characterization and forecast of karst systems - Alireza Kavousi; Thomas Reimann; Thomas Wöhling; Steffen Birk; Andrew J. Luhmann; Jannes Kordilla; Torsten Noffz; Martin Sauter; Rudolf Liedl (Hydrogeology Journal, 2023)
Characterization of karst systems and forecast of their state variables are essential for groundwater management and engineering in karst regions. These objectives can be met by the use of process-based discrete-continuum models (DCMs). However, results of DCMs may suffer from inversion nonuniqueness. It has been demonstrated that the joint inversion of observations regulated by different natural processes can tackle the nonuniqueness issue in groundwater modeling. However, this has not been tested for DCMs thus far. This research proposes a methodology for the joint inversion of hydro-thermo-chemo-graphs, applying to two small-scale sink-to-spring experiments at Freiheit Spring, Minnesota, USA. In order to address conceptual uncertainty, a multimodel approach was implemented, featuring seven mutually exclusive variants. Spring hydro-thermo-chemo-graphs, for all the variants simulated by MODFLOW-CFPv2, were jointly inverted using a weighted least squares algorithm. Subsequently, models were compared in terms of inversion and forecast performances, as well as parameter uncertainties. Results reveal the suitability of the DCM approach for simultaneous inversion and forecast of hydro-physico-chemical behavior of karst systems, even at a scale of meters and seconds. The estimated volume of the tracer conduit passage ranges from approximately 46–51 m 3 , which is comparable to the estimate from the flood-pulse method. Moreover, it was demonstrated that the thermograph and hydrograph contain more information about aquifer characteristics than the chemograph. However, this finding can be site-specific and should depend on the analysis scale, the considered conceptual models, and the hydrological state, which are potentially affected by minor unaccountable processes and features.

Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community - Zillur Rahman; Weijia Liu; Lara Stapleton; Nikki Kenters; Dewa A.P. Rasmika Dewi; Ori Gudes; Helen Ziochos; Stuart J. Khan; Kaye Power; Mary-Louise McLaws; Torsten Thomas (Environmental Pollution, 2023)

The role of systematics for understanding ecosystem functions: Proceedings of the Zoologica Scripta Symposium, Oslo, Norway, 25 August 2022 - Lutz Bachmann; Jan Beermann; Thomas Brey; Hugo J. de Boer; Jennifer Dannheim; Bente Edvardsen; Per G. P. Ericson; Kevin C. Holston; Veronika A. Johansson; Paul Kloss; Rebecca Konijnenberg; Karen J. Osborn; et al. (Zoologica Scripta, 2023)
On 25 August 2022, the Zoologica Scripta ‐ An International Journal of Systematic Zoology and the Norwegian Academy of Sciences and Letters arranged a symposium entitled ‘The role of systematics for understanding ecosystem functions’ in the Academy's premises in Oslo, Norway. The symposium aimed at offering a forum for exploring and discussing trends and future developments in the field of systematics. Eleven international experts contributed expertise on various issues related to global challenges, such as biodiversity assessments, databases, cutting‐edge analysis tools, and the consequences of the taxonomic impediment. Here, we compiled a multi‐author proceedings paper of the symposium contributions that are arranged in chapters and presents the content and the key conclusions of the majority of the presentations.

Toxic effect of cigarette butts leachates on blood markers of Periophthalmus waltoni species from the Persian Gulf region - Farshid Soleimani; Sina Dobaradaran; Gholamhossein Mohebbi; Amir Vazirizadeh; Gabriel E. De-la-Torre; Reza Saeedi; Iraj Nabipour; Thomas E. Novotny; Torsten C. Schmidt (Chemosphere, 2023)

Functional characterization and taxonomic classification of novel gammaproteobacterial diversity in sponges - Viet Hung Nguyen; Bernd Wemheuer; Weizhi Song; Holly Bennett; Giorgia Palladino; Ilia Burgsdorf; Sofia Sizikov; Laura Steindler; Nicole S. Webster; Torsten Thomas (Systematic and Applied Microbiology, 2023)

Diverse Effects of Climate, Land Use, and Insects on Dung and Carrion Decomposition - Jana Englmeier; Oliver Mitesser; M. Eric Benbow; Torsten Hothorn; Christian von Hoermann; Caryl Benjamin; Ute Fricke; Cristina Ganuza; Maria Haensel; Sarah Redlich; Rebekka Riebl; Sandra Rojas Botero; et al. (Ecosystems, 2023)
Land-use intensification and climate change threaten ecosystem functions. A fundamental, yet often overlooked, function is decomposition of necromass. The direct and indirect anthropogenic effects on decomposition, however, are poorly understood. We measured decomposition of two contrasting types of necromass, rat carrion and bison dung, on 179 study sites in Central Europe across an elevational climate gradient of 168–1122 m a.s.l. and within both local and regional land uses. Local land-use types included forest, grassland, arable fields, and settlements and were embedded in three regional land-use types (near-natural, agricultural, and urban). The effects of insects on decomposition were quantified by experimental exclusion, while controlling for removal by vertebrates. We used generalized additive mixed models to evaluate dung weight loss and carrion decay rate along elevation and across regional and local land-use types. We observed a unimodal relationship of dung decomposition with elevation, where greatest weight loss occurred between 600 and 700 m, but no effects of local temperature, land use, or insects. In contrast to dung, carrion decomposition was continuously faster with both increasing elevation and local temperature. Carrion reached the final decomposition stage six days earlier when insect access was allowed, and this did not depend on land-use effect. Our experiment identified different major drivers of decomposition on each necromass form. The results show that dung and carrion decomposition are rather robust to local and regional land use, but future climate change and decline of insects could alter decomposition processes and the self-regulation of ecosystems.

Enhancing the structural diversity between forest patches—A concept and real‐world experiment to study biodiversity, multifunctionality and forest resilience across spatial scales - Jörg Müller; Oliver Mitesser; Marc W. Cadotte; Fons van der Plas; Akira S. Mori; Christian Ammer; Anne Chao; Michael Scherer‐Lorenzen; Petr Baldrian; Claus Bässler; Peter Biedermann; Simone Cesarz; et al. (Global Change Biology, 2023)
Intensification of land use by humans has led to a homogenization of landscapes and decreasing resilience of ecosystems globally due to a loss of biodiversity, including the majority of forests. Biodiversity–ecosystem functioning (BEF) research has provided compelling evidence for a positive effect of biodiversity on ecosystem functions and services at the local (α‐diversity) scale, but we largely lack empirical evidence on how the loss of between‐patch β‐diversity affects biodiversity and multifunctionality at the landscape scale (γ‐diversity). Here, we present a novel concept and experimental framework for elucidating BEF patterns at α‐, β‐, and γ‐scales in real landscapes at a forest management‐relevant scale. We examine this framework using 22 temperate broadleaf production forests, dominated by Fagus sylvatica . In 11 of these forests, we manipulated the structure between forest patches by increasing variation in canopy cover and deadwood. We hypothesized that an increase in landscape heterogeneity would enhance the β‐diversity of different trophic levels, as well as the β‐functionality of various ecosystem functions. We will develop a new statistical framework for BEF studies extending across scales and incorporating biodiversity measures from taxonomic to functional to phylogenetic diversity using Hill numbers. We will further expand the Hill number concept to multifunctionality allowing the decomposition of γ‐multifunctionality into α‐ and β‐components. Combining this analytic framework with our experimental data will allow us to test how an increase in between patch heterogeneity affects biodiversity and multifunctionality across spatial scales and trophic levels to help inform and improve forest resilience under climate change. Such an integrative concept for biodiversity and functionality, including spatial scales and multiple aspects of diversity and multifunctionality as well as physical and environmental structure in forests, will go far beyond the current widely applied approach in forestry to increase resilience of future forests through the manipulation of tree species composition.

Protein fractionation and shotgun proteomics analysis of enriched bacterial cultures shed new light on the enzymatically catalyzed degradation of acesulfame - Sandro Castronovo; Lissa Helmholz; David Wolff; Jan Struckmann Poulsen; Jeppe Lund Nielsen; Thomas A. Ternes; Torsten C. Schmidt; Arne Wick (Water Research, 2023)

Chemical contents and toxicity of cigarette butts leachates in aquatic environment: A case study from the Persian Gulf region - Farshid Soleimani; Sina Dobaradaran; Amir Vazirizadeh; Gholamhossein Mohebbi; Bahman Ramavandi; Gabriel E. De-la-Torre; Iraj Nabipour; Torsten C. Schmidt; Thomas E. Novotny; Ammar Maryamabadi; Zahra Kordrostami (Chemosphere, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Correction to: Spatial variation of rodenticides and emerging contaminants in blood of raptor nestlings from Germany - Alexander Badry; Detlef Schenke; Helmut Brücher; Nayden Chakarov; Thomas Grünkorn; Hubertus Illner; Oliver Krüger; Torsten Marczak; Gerard Müskens; Winfried Nachtigall; Ronald Zollinger; Gabriele Treu; et al. (Environmental Science and Pollution Research, 2022)

Spatial variation of rodenticides and emerging contaminants in blood of raptor nestlings from Germany - Alexander Badry; Detlef Schenke; Helmut Brücher; Nayden Chakarov; Thomas Grünkorn; Hubertus Illner; Oliver Krüger; Torsten Marczak; Gerard Müskens; Winfried Nachtigall; Ronald Zollinger; Gabriele Treu; et al. (Environmental Science and Pollution Research, 2022)
Wildlife exposures to pest controlling substances have resulted in population declines of many predatory species during the past decades. Many pesticides were subsequently classified as persistent, bioaccumulative, and toxic (PBT) and banned on national or global scales. However, despite their risks for non-target vertebrate wildlife, PBT substances such as anticoagulant rodenticides (ARs) are still permitted for use in Europe and have shown to threaten raptors. Whereas risks of ARs are known, much less information is available on emerging agrochemicals such as currently used PPPs and medicinal products (MPs) in higher trophic level species. We expect that currently used PPPs are relatively mobile (vs. lipophilic) as a consequence of the PBT criteria and thus more likely to be present in aqueous matrices. We therefore analyzed blood of 204 raptor nestlings of three terrestrial (red kite, common buzzard, Montagu’s harrier) and two aquatic species (white-tailed sea eagle, osprey) from Germany. In total, we detected ARs in 22.6% of the red kites and 8.6% of the buzzards, whereas no Montagu’s harriers or aquatic species were exposed prior to sampling. ΣAR concentration tended to be higher in North Rhine-Westphalia (vs. North-Eastern Germany) where population density is higher and intense livestock farming more frequent. Among the 90 targeted and currently used PPPs, we detected six substances from which bromoxynil (14.2%) was most frequent. Especially Montagu’s harrier (31%) and red kites (22.6%) were exposed and concentrations were higher in North Rhine-Westphalia as well. Among seven MPs, we detected ciprofloxacin (3.4%), which indicates that risk mitigation measures may be needed as resistance genes were already detected in wildlife from Germany. Taken together, our study demonstrates that raptors are exposed to various chemicals during an early life stage depending on their sampling location and underpins that red kites are at particular risk for multiple pesticide exposures in Germany.

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Environmental filtering drives assembly of diatom communities over evolutionary time‐scales - Elena Jovanovska; Torsten Hauffe; Björn Stelbrink; Aleksandra Cvetkoska; Zlatko Levkov; Bernd Wagner; Jack H. Lacey; Nadja Ognjanova‐Rumenova; Paul B. Hamilton; Karen M. Brandenburg; Christian Albrecht; Thomas Wilke (Global Ecology and Biogeography, 2022)
Aim Ecological communities are structured through the interplay of deterministic assembly processes such as competition and environmental filtering. Whereas the drivers of spatial community structure are frequently studied in extant communities, little is known about the relative importance of assembly processes in response to environmental factors over evolutionary time‐scales. Here, we use an integrative framework to unravel community assembly processes since the inception of a long‐lived lake ecosystem. Location Lake Ohrid. Time period From lake formation 1.36 million years ago to the present. Major taxa studied Planktonic diatoms. Methods We constructed a dated phylogeny of extant and extinct diatoms and collected trait data for 380 fossil communities to quantify phylogenetic community structure and functional richness and to determine the relative importance of deterministic assembly processes over time. We then used regression analysis to correlate the phylogenetic community structure with palaeoenvironmental and intrinsic biological predictors and to identify primary drivers of assembly processes. Results Our results suggest a dense packing of niche space with higher species richness and co‐occurrence of closely related species. There are only two short episodes in the very recent past dominated by distantly related taxa. We found distinct changes in phylogenetic community structure upon speciation or extinction events and an increase in mean community relatedness over time. Main conclusions Our finding of closely related co‐occurring species implies environmental filtering as the primary assembly mechanism, with a minor but increasingly important role of competition towards the present, driven by evolutionary dynamics. Such an increase in the relative contribution of competition to the assembly of communities in relation to the aging of an insular ecosystem, together with a denser packing of morphospace in the early phase of system ontogeny is compatible with ecological predictions according to the theory of island biogeography.

Communality in microbial stress response and differential metabolic interactions revealed by time‐series analysis of sponge symbionts - Jessica A. Taylor; Cristina Díez‐Vives; Shaun Nielsen; Bernd Wemheuer; Torsten Thomas (Environmental Microbiology, 2022)
Summary The diversity and function of sponge‐associated symbionts is now increasingly understood; however, we lack an understanding of how they dynamically behave to ensure holobiont stability in the face of environmental variation. Here, we performed a metatransciptomic analysis on three microbial symbionts of the sponge Cymbastela concentrica in situ over 14 months and through differential gene expression and correlation analysis to environmental variables uncovered differences that speak to their metabolic activities and level of symbiotic and environmental interactions. The nitrite‐oxidizing Ca . Porinitrospira cymbastela maintained a seemingly stable metabolism, with the few differentially expressed genes related only to stress responses. The heterotrophic Ca . Porivivens multivorans displayed differential use of holobiont‐derived compounds and respiration modes, while the ammonium‐oxidizing archaeon Ca . Nitrosopumilus cymbastelus differentially expressed genes related to phosphate metabolism and symbiosis effectors. One striking similarity between the symbionts was their similar variation in expression of stress‐related genes. Our time‐series study showed that the microbial community of C. concentrica undertakes dynamic gene expression adjustments in response to the surroundings, tuned to deal with general stress and metabolic interactions between holobiont members. The success of these dynamic adjustments likely underpins the stability of the sponge holobiont and may provide resilience against environmental change.

Development of ULYSSIS, a Tool for the Biosynthesis of Cyclotides and Cyclic Knottins - Thomas N. G. Handley; Torsten Kleffmann; Margi I. Butler (International Journal of Peptide Research and Therapeutics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Performance of a SARS CoV-2 antibody ELISA based on simultaneous measurement of antibodies against the viral nucleoprotein and receptor-binding domain - Nina Reiners; Carolin Schnurra; Henning Trawinski; Judith Kannenberg; Thomas Hermsdorf; Andrea Aebischer; Torsten Schöneberg; Sven Reiche; Christian Jassoy (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS CoV-2 antibody assays measure antibodies against the viral nucleoprotein (NP) or spike protein. The study examined if testing of antibodies against both antigens increases the diagnostic sensitivity. Sera (N=98) from infected individuals were tested with ELISAs based on the NP, receptor-binding domain (RBD), or both proteins. The AUROCs were 0.958 (NP), 0.991 (RBD), and 0.992 (NP/RBD). The RBD- and NP/RBD-based ELISAs showed better performance than the NP-based assay. Simultaneous testing for antibodies against NP and RBD increased the number of true and false positives. If maximum diagnostic sensitivity is required, the NP/RBD-based ELISA is preferable. Otherwise, the RBD-based ELISA is sufficient.

Climate hazard indices projections based on CORDEX-CORE, CMIP5 and CMIP6 ensemble - Erika Coppola; Francesca Raffaele; Filippo Giorgi; Graziano Giuliani; Gao Xuejie; James M. Ciarlo; Taleena Rae Sines; José Abraham Torres-Alavez; Sushant Das; Fabio di Sante; Emanuela Pichelli; Russell Glazer; et al. (Climate Dynamics, 2021)

Assessing mean climate change signals in the global CORDEX-CORE ensemble - Claas Teichmann; Daniela Jacob; Armelle Reca Remedio; Thomas Remke; Lars Buntemeyer; Peter Hoffmann; Arne Kriegsmann; Ludwig Lierhammer; Katharina Bülow; Torsten Weber; Kevin Sieck; Diana Rechid; et al. (Climate Dynamics, 2021)
The new Coordinated Output for Regional Evaluations (CORDEX-CORE) ensemble provides high-resolution, consistent regional climate change projections for the major inhabited areas of the world. It serves as a solid scientific basis for further research related to vulnerability, impact, adaptation and climate services in addition to existing CORDEX simulations. The aim of this study is to investigate and document the climate change information provided by the CORDEX-CORE simulation ensemble, as a part of the World Climate Research Programme (WCRP) CORDEX community. An overview of the annual and monthly mean climate change information in selected regions in different CORDEX domains is presented for temperature and precipitation, providing the foundation for detailed follow-up studies and applications. Initially, two regional climate models (RCMs), REMO and RegCM were used to downscale global climate model output. The driving simulations by AR5 global climate models (AR5-GCMs) were selected to cover the spread of high, medium, and low equilibrium climate sensitivity at a global scale. The CORDEX-CORE ensemble has doubled the spatial resolution compared to the previously existing CORDEX simulations in most of the regions (25 $$\,km$$ km (0.22 $$^{° }$$ ∘ ) versus 50 $$\,km$$ km (0.44 $$^{° }$$ ∘ )) leading to a potentially improved representation of, e.g., physical processes in the RCMs. The analysis focuses on changes in the IPCC physical climate reference regions. The results show a general reasonable representation of the spread of the temperature and precipitation climate change signals of the AR5-GCMs by the CORDEX-CORE simulations in the investigated regions in all CORDEX domains by mostly covering the AR5 interquartile range of climate change signals. The simulated CORDEX-CORE monthly climate change signals mostly follow the AR5-GCMs, although for specific regions they show a different change in the course of the year compared to the AR5-GCMs, especially for RCP8.5, which needs to be investigated further in region specific process studies.

A new spatially distributed added value index for regional climate models: the EURO-CORDEX and the CORDEX-CORE highest resolution ensembles - James M. Ciarlo`; Erika Coppola; Adriano Fantini; Filippo Giorgi; XueJie Gao; Yao Tong; Russell H. Glazer; Jose Abraham Torres Alavez; Taleena Sines; Emanuela Pichelli; Francesca Raffaele; Sushant Das; et al. (Climate Dynamics, 2021)

Characterization of a novel roseophage and the morphological and transcriptional response of the sponge symbiont Ruegeria AU67 to infection - Lisa Baum; Mary T. H. D. Nguyen; Yunke Jia; Joanna Biazik; Torsten Thomas (Environmental Microbiology, 2021)
Summary Sponges have recently been recognized to contain complex communities of bacteriophages; however, little is known about how they interact with their bacterial hosts. Here, we isolated a novel phage, called Ruegeria phage Tedan, and characterized its impact on the bacterial sponge symbiont Ruegeria AU67 on a morphological and molecular level. Phage Tedan was structurally, genomically and phylogenetically characterized to be affiliated with the genus Xiamenvirus of the family Siphoviridae . Through microscopic observations and transcriptomic analysis, we show that phage Tedan upon infection induces a process leading to metabolic and morphological changes in its host. These changes would render Ruegeria AU67 better adapted to inhabit the sponge holobiont due to an improved utilization of ecologically relevant energy and carbon sources as well as a potential impediment of phagocytosis by the sponge through cellular enlargement. An increased survival or better growth of the bacterium in the sponge environment will likely benefit the phage reproduction. Our results point towards the possibility that phages from host‐associated environments require, and have thus evolved, different strategies to interact with their host when compared to those phages from free‐living or planktonic environments.

Rapid response flow cytometric assay for the detection of antibody responses to SARS-CoV-2 - Dennis Lapuente; Clara Maier; Pascal Irrgang; Julian Hübner; Antonia Sophia Peter; Markus Hoffmann; Armin Ensser; Katharina Ziegler; Thomas H. Winkler; Torsten Birkholz; Andreas E. Kremer; Philipp Steininger; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 has emerged as a previously unknown zoonotic coronavirus that spread worldwide causing a serious pandemic. While reliable nucleic acid–based diagnostic assays were rapidly available, only a limited number of validated serological assays were available in the early phase of the pandemic. Here, we evaluated a novel flow cytometric approach to assess spike-specific antibody responses.HEK 293T cells expressing SARS-CoV-2 spike protein in its natural confirmation on the surface were used to detect specific IgG and IgM antibody responses in patient sera by flow cytometry. A soluble angiotensin-converting-enzyme 2 (ACE-2) variant was developed as external standard to quantify spike-specific antibody responses on different assay platforms. Analyses of 201 pre-COVID-19 sera proved a high assay specificity in comparison to commercially available CLIA and ELISA systems, while also revealing the highest sensitivity in specimens from PCR-confirmed SARS-CoV-2-infected patients. The external standard allowed robust quantification of antibody responses among different assay platforms. In conclusion, our newly established flow cytometric assay allows sensitive and quantitative detection of SARS-CoV-2-specific antibodies, which can be easily adopted in different laboratories and does not rely on external supply of assay kits. The flow cytometric assay also provides a blueprint for rapid development of serological tests to other emerging viral infections

Low-quality animal by-product streams for the production of PHA-biopolymers: fats, fat/protein-emulsions and materials with high ash content as low-cost feedstocks - Victoria Saad; Björn Gutschmann; Thomas Grimm; Torsten Widmer; Peter Neubauer; Sebastian L. Riedel (Biotechnology Letters, 2021)
Objective The rapid accumulation of crude-oil based plastics in the environment is posing a fundamental threat to the future of mankind. The biodegradable and bio-based polyhydroxyalkanoates (PHAs) can replace conventional plastics, however, their current production costs are not competitive and therefore prohibiting PHAs from fulfilling their potential. Results Different low-quality animal by-products, which were separated by thermal hydrolysis into a fat-, fat/protein-emulsion- and mineral-fat-mixture- (material with high ash content) phase, were successfully screened as carbon sources for the production of PHA. Thereby, Ralstonia eutropha Re2058/pCB113 accumulated the short- and medium-chain-length copolymer poly(hydroxybutyrate- co -hydroxyhexanoate) [P(HB- co -HHx)]. Up to 90 wt% PHA per cell dry weight with HHx-contents of 12–26 mol% were produced in shake flask cultivations. Conclusion In future, the PHA production cost could be lowered by using the described animal by-product streams as feedstock. Graphical abstract

Impact of phosphodiesterases PDE3 and PDE4 on 5-hydroxytryptamine receptor4-mediated increase of cAMP in human atrial fibrillation - Bernardo Dolce; Torsten Christ; Nefeli Grammatika Pavlidou; Yalin Yildirim; Hermann Reichenspurner; Thomas Eschenhagen; Viacheslav O. Nikolaev; Alberto J Kaumann; Cristina E Molina (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Atrial fibrillation (AF)–associated remodeling includes contractile dysfunction whose reasons are only partially resolved. Serotonin (5-HT) increases contractile force and causes arrhythmias in atrial trabeculae from patients in sinus rhythm (SR). In persistent atrial fibrillation (peAF), the force responses to 5-HT are blunted and arrhythmic effects are abolished. Since force but not arrhythmic responses to 5-HT in peAF could be restored by PDE3 + PDE4 inhibition, we sought to perform real-time measurements of cAMP to understand whether peAF alters PDE3 + PDE4-mediated compartmentation of 5-HT 4 receptor-cAMP responses. Isolated human atrial myocytes from patients in SR, with paroxysmal AF (paAF) or peAF, were adenovirally transduced to express the FRET-based cAMP sensor Epac1-camps. Forty-eight hours later, cAMP responses to 5-HT (100 μM) were measured in the absence or concomitant presence of the PDE3 inhibitor cilostamide (0.3 μM) and the PDE4 inhibitor rolipram (1 μM). We successfully established real-time cAMP imaging in AF myocytes. 5-HT increased cAMP in SR, paAF, and peAF, but in line with previous findings on contractility, this increase was considerably smaller in peAF than in SR or paAF. The maximal cAMP response to forskolin (10 μM) was preserved in all groups. The diminished cAMP response to 5-HT in peAF was recovered by preincubation with cilostamide + rolipram. We uncovered a significantly diminished cAMP response to 5-HT 4 receptor stimulation which may explain the blunted 5-HT inotropic responses observed in peAF. Since both cAMP and force responses but not arrhythmic responses were recovered after concomitant inhibition of PDE3 + PDE4, they might be regulated in different subcellular microdomains.

Engineered biosynthesis of cyclotides - Thomas N. G. Handley; Hyon-Xhi Tan; Malcolm T. Rutledge; Hans Henning Brewitz; Joel D. A. Tyndall; Torsten Kleffmann; Margi I. Butler; Russell T. M. Poulter; Sigurd M. Wilbanks (New Zealand Journal of Botany, 2020)

Assessing the strength and sensitivity of the core microbiota approach on a highly diverse sponge reef - Carmen Astudillo‐García; James J. Bell; Jose M. Montoya; Lucas Moitinho‐Silva; Torsten Thomas; Nicole S. Webster; Michael W. Taylor (Environmental Microbiology, 2020)
Summary Marine sponge reefs usually comprise a complex array of taxonomically different sponge species, many of these hosting highly diverse microbial communities. The number of microbial species known to occupy a given sponge ranges from tens to thousands, bringing numerous challenges to their analysis. One way to deal with such complexity is to use a core microbiota approach, in which only prevalent and abundant microbes are considered. Here we aimed to test the strength and sensitivity of the core microbiota approach by applying different core definitions to 20 host sponge species. Application of increasingly stringent relative abundance and/or percentage occurrence thresholds to qualify as part of the core microbiota decreased the number of ‘core’ OTUs and phyla and, consequently, changed both alpha‐ and beta‐diversity patterns. Moreover, microbial co‐occurrence patterns explored using correlation networks were also affected by the core microbiota definition. The application of stricter thresholds resulted in smaller and less compartmentalized networks, with different keystone species. These results highlight that the application of different core definitions to phylogenetically disparate host species can result in the drawing of markedly different conclusions. Consequently, we recommend to assess the effects of different core community definitions on the specific system of study before considering its application.

Holocene variability in climate and oceanic conditions in the winter rainfall zone of South Africa—inferred from a high resolution diatom record from Verlorenvlei - Kelly L. Kirsten; Thomas Kasper; Hayley C. Cawthra; Paul Strobel; Lynne J. Quick; Michael E. Meadows; Torsten Haberzettl (Journal of Quaternary Science, 2020)
We present a diatom record from a well‐dated 15.25 m composite sedimentary core from Verlorenvlei, a shallow coastal lake on the west coast of South Africa. We show that fluctuations in the diatom record occur in response to changes in sea level, ocean–atmosphere interactions and latitudinal shifts in the wind belts. During the early to mid‐Holocene, the system primarily responds to sea level changes. A marine community that favours high nutrients is evident, particularly during 9200–8000, 7420–7000 and 6200–5600 cal a bp , corroborating periods of Benguela upwelling linked to fluctuations in the southeast trade winds. Increases in bioproductivity (%TOC, C/N) and fresher‐water diatoms are associated with wetter conditions over the region and the northward migration of the southern westerly wind belt, most notably between 8000 and 7500 cal a bp and over the last 700 years. The latter trends are concomitant with changes in the extent of Antarctic sea ice and availability of moisture in southern South America. During the late Holocene, as sea levels stabilised to modern levels, climate variability is more strongly evident. The body of evidence further reveals the sensitivity of the region to high‐latitude atmospheric mechanisms, but also showcases the significance of the southeast trade winds.

Climatology of Transient Luminous Events and Lightning Observed Above Europe and the Mediterranean Sea - Enrico Arnone; József Bór; Olivier Chanrion; Veronika Barta; Stefano Dietrich; Carl-Fredrik Enell; Thomas Farges; Martin Füllekrug; Antti Kero; Roberto Labanti; Antti Mäkelä; Keren Mezuman; et al. (Surveys in Geophysics, 2020)

Natural and Regenerated Saltmarshes Exhibit Similar Soil and Belowground Organic Carbon Stocks, Root Production and Soil Respiration - Nadia S. Santini; Catherine E. Lovelock; Quan Hua; Atun Zawadzki; Debashish Mazumder; Tim R. Mercer; Miriam Muñoz-Rojas; Simon A. Hardwick; Bindu Swapna Madala; William Cornwell; Torsten Thomas; Ezequiel M. Marzinelli; et al. (Ecosystems, 2019)

Measuring continuous compositional change using decline and decay in zeta diversity - Melodie A. McGeoch; Guillaume Latombe; Nigel R. Andrew; Shinichi Nakagawa; David A. Nipperess; Mariona Roigé; Ezequiel M. Marzinelli; Alexandra H. Campbell; Adriana Vergés; Torsten Thomas; Peter D. Steinberg; Katherine E. Selwood; et al. (Ecology, 2019)
Incidence, or compositional, matrices are generated for a broad range of research applications in biology. Zeta diversity provides a common currency and conceptual framework that links incidence‐based metrics with multiple patterns of interest in biology, ecology, and biodiversity science. It quantifies the variation in species (or OTU ) composition of multiple assemblages (or cases) in space or time, to capture the contribution of the full suite of narrow, intermediate, and wide‐ranging species to biotic heterogeneity. Here we provide a conceptual framework for the application and interpretation of patterns of continuous change in compositional diversity using zeta diversity. This includes consideration of the survey design context, and the multiple ways in which zeta diversity decline and decay can be used to examine and test turnover in the identity of elements across space and time. We introduce the zeta ratio–based retention rate curve to quantify rates of compositional change. We illustrate these applications using 11 empirical data sets from a broad range of taxa, scales, and levels of biological organization—from DNA molecules and microbes to communities and interaction networks—including one of the original data sets used to express compositional change and distance decay in ecology. We show (1) how different sample selection schemes used during the calculation of compositional change are appropriate for different data types and questions, (2) how higher orders of zeta may in some cases better detect shifts and transitions, and (3) the relative roles of rare vs. common species in driving patterns of compositional change. By exploring the application of zeta diversity decline and decay, including the retention rate, across this broad range of contexts, we demonstrate its application for understanding continuous turnover in biological systems.

N2O emissions from a loamy soil cropped with winter wheat as affected by N-fertilizer amount and nitrification inhibitor - Ivan Guzman-Bustamante; Thomas Winkler; Rudolf Schulz; Torsten Müller; Thomas Mannheim; Juan Carlos Laso Bayas; Reiner Ruser (Nutrient Cycling in Agroecosystems, 2019)

Impact of Harvest Date and Cutting Length of Grass Ley and Whole-Crop Cereals on Methane Yield and Economic Viability as Feedstock for Biogas Vehicle Fuel Production - Thomas Prade; Sven-Erik Svensson; Torsten Hörndahl; Emma Kreuger (BioEnergy Research, 2019)

Can plant phenolic compounds reduce Fusarium growth and mycotoxin production in cereals? - Torsten Schöneberg; Karin Kibler; Michael Sulyok; Tomke Musa; Thomas D. Bucheli; Fabio Mascher; Mario Bertossa; Ralf T. Voegele; Susanne Vogelgsang (Food Additives & Contaminants: Part A, 2018)

Correction to: Seismicity in the block mountains between Halle and Leipzig, Central Germany: centroid moment tensors, ground motion simulation, and felt intensities of two M ≈ 3 earthquakes in 2015 and 2017 - Torsten Dahm; Sebastian Heimann; Sigward Funke; Siegfried Wendt; Ivo Rappsilber; Dino Bindi; Thomas Plenefisch; Fabrice Cotton (Journal of Seismology, 2018)

Essential Gene Clusters Identified in Stenotrophomonas MB339 for Multiple Metal/Antibiotic Resistance and Xenobiotic Degradation - Fozia Aslam; Azra Yasmin; Torsten Thomas (Current Microbiology, 2018)

Infection conditions of Fusarium graminearum in barley are variety specific and different from those in wheat - Torsten Schöneberg; Tomke Musa; Hans-Rudolf Forrer; Fabio Mascher; Thomas D. Bucheli; Mario Bertossa; Beat Keller; Susanne Vogelgsang (European Journal of Plant Pathology, 2018)

Seismicity in the block mountains between Halle and Leipzig, Central Germany: centroid moment tensors, ground motion simulation, and felt intensities of two M ≈ 3 earthquakes in 2015 and 2017 - Torsten Dahm; Sebastian Heimann; Sigward Funke; Siegfried Wendt; Ivo Rappsilber; Dino Bindi; Thomas Plenefisch; Fabrice Cotton (Journal of Seismology, 2018)

Functional biogeography and host specificity of bacterial communities associated with the Marine Green Alga Ulva spp. - Alexandra J. Roth‐Schulze; José Pintado; Enrique Zozaya‐Valdés; Javier Cremades; Patricia Ruiz; Staffan Kjelleberg; Torsten Thomas (Molecular Ecology, 2018)
Bacterial communities play an essential role for the function of marine macroalgae. Recent work has shown that bacterial communities associated with individual macroalgae possess on a local scale a functional core that is likely derived from diverse members of functional guilds. It is not known whether such functional cores also exist across large spatial scales or between closely related host species. To address this, we studied here the bacterial communities on three species of the green macroalgal genus Ulva from different geographic locations. While the taxonomic composition was too variable to describe a community core, we identified genes that were enriched across all Ulva samples as compared to the communities of the surrounding seawater. Of these core functions, 70% were consistently found and independent of the Ulva species and biogeography, while the remaining functions (~30%) are possibly involved in local or host‐specific adaptations. For each host individual, the core functions are provided by bacteria with distinct phylogenetic origin and these bacteria could constitute a global guild of Ulva ‐associated bacteria. Together, our results demonstrate the presence of a stable core set of functional genes in the bacterial communities associated with closely related host species and across large biogeographies.

Novel ssDNA Viruses Detected in the Virome of Bleached, Habitat-Forming Kelp Ecklonia radiata - Douglas T. Beattie; Tim Lachnit; Elizabeth A. Dinsdale; Torsten Thomas; Peter D. Steinberg (Frontiers in Marine Science, 2018)

Effects of different C/N ratios on bacterial compositions and processes in an organically managed soil - Jun Ye; Pablo Gonzalez Perez; Rui Zhang; Shaun Nielsen; Danfeng Huang; Torsten Thomas (Biology and Fertility of Soils, 2018)

The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia - Alexandra J. Roth‐Schulze; Torsten Thomas; Peter Steinberg; Marty R. Deveney; Jason E. Tanner; Kathryn H. Wiltshire; Stephanie Papantoniou; John W. Runcie; C. Frederico D. Gurgel (Limnology and Oceanography, 2018)
Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia , one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO 2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.

Diversity studies in genetic resources of Solanum spp. (section Petota) by comparative application of ISAP markers - Kerstin Diekmann; Kathrin M. Seibt; Katja Muders; Torsten Wenke; Holger Junghans; Thomas Schmidt; Klaus J. Dehmer (Genetic Resources and Crop Evolution, 2017)

Fractionation of sulfur (S) in beech (Fagus sylvatica) forest soils in relation to distance from the stem base as useful tool for modeling S biogeochemistry - Ondrej Hanousek; Thomas Prohaska; Martin Kulhanek; Jiri Balik; Vaclav Tejnecky; Torsten W. Berger (Modeling Earth Systems and Environment, 2017)

Microbial community function in the bleaching disease of the marine macroalgae Delisea pulchra - Enrique Zozaya‐Valdés; Alexandra J. Roth‐Schulze; Suhelen Egan; Torsten Thomas (Environmental Microbiology, 2017)
Summary Disease is increasingly viewed as a major factor impacting the health of both natural and cultured populations of marine organisms, including macroalgae. The red macroalga Delisea pulchra suffers from a bleaching disease resulting from host stress and infection by opportunistic bacterial pathogens. However, how pathogens cause the disease and how the entire macro algal‐associated community is involved in the process is unclear. Here, we perform a metagenomic analysis of microbial communities associated with diseased and healthy D. pulchra across multiple bleaching events. Analysis of reconstructed 16S rRNA gene sequences showed that bacteria belonging to the families Rhodobacteraceae , Saprospiraceae and Flavobacteriaceae , including bacteria previously implicated in algal bleaching, to be enriched in diseased D. pulchra . Genes with predicted functions related to chemotaxis, motility, oxidative stress response, vitamin biosynthesis and nutrient acquisition were also prevalent in microbiomes of bleached algae, which may have a role in pathogenicity. Reconstruction of genomes that were abundant on bleached samples revealed that no single organism contains all bleaching‐enriched functional genes. This observation indicates that potential virulence traits are distributed across multiple bacteria and that the disease in D. pulchra may result from a consortium of opportunistic pathogens, analogous to dysbiotic or polymicrobial diseases.

Thiol-ene Clickable Poly(glycidol) Hydrogels for Biofabrication - Simone Stichler; Tomasz Jungst; Martha Schamel; Ilona Zilkowski; Matthias Kuhlmann; Thomas Böck; Torsten Blunk; Jörg Teßmar; Jürgen Groll (Annals of Biomedical Engineering, 2017)

Partitioning of functional and taxonomic diversity in surface‐associated microbial communities - Alexandra J. Roth‐Schulze; Enrique Zozaya‐Valdés; Peter D. Steinberg; Torsten Thomas (Environmental Microbiology, 2016)
Summary Surfaces, including those submerged in the marine environment, are subjected to constant interactions and colonisation by surrounding microorganisms. The principles that determine the assembly of those epibiotic communities are however poorly understood. In this study, we employed a hierarchical design to assess the functionality and diversity of microbial communities on different types of host surfaces (e.g. macroalgae, seagrasses). We found that taxonomic diversity was unique to each type of host, but that the majority of functions (> 95%) could be found in any given surface community, suggesting a high degree of functional redundancy. However, some community functions were enriched on certain surfaces and were related to host‐specific properties (e.g. the degradation of specific polysaccharides). Together these observations support a model, whereby communities on surfaces are assembled from guilds of microorganisms with a functionality that is partitioned into general properties for a surface‐associated life‐style, but also specific features that mediate host‐specificity.

Multiple opportunistic pathogens can cause a bleaching disease in the red seaweed Delisea pulchra - Vipra Kumar; Enrique Zozaya‐Valdes; Staffan Kjelleberg; Torsten Thomas; Suhelen Egan (Environmental Microbiology, 2016)
Summary While macroalgae (or seaweeds) are increasingly recognized to suffer from disease, in most cases the causative agents are unknown. The model macroalga Delisea pulchra is susceptible to a bleaching disease and previous work has identified two epiphytic bacteria, belonging to the Roseobacter clade, that cause bleaching under laboratory conditions. However, recent environmental surveys have shown that these in vitro pathogens are not abundant in naturally bleached D. pulchra , suggesting the presence of other pathogens capable of causing this algal disease. To test this hypothesis, we cultured bacteria that were abundant on bleached tissue across multiple disease events and assessed their ability to cause bleaching disease. We identified the new pathogens Alteromonas sp. BL110, Aquimarina sp. AD1 and BL5 and Agarivorans sp BL7 that are phylogenetically diverse, distinct from the previous two pathogens and can also be found in low abundance in healthy individuals. Moreover, we found that bacterial communities of diseased individuals that were infected with these pathogens were less diverse and more divergent from each other than those of healthy algae. This study demonstrates that multiple and opportunistic pathogens can cause the same disease outcome for D. pulchra and we postulate that such pathogens are more common in marine systems than previously anticipated.

Fusarium and mycotoxin spectra in Swiss barley are affected by various cropping techniques - Torsten Schöneberg; Charlotte Martin; Felix E. Wettstein; Thomas D. Bucheli; Fabio Mascher; Mario Bertossa; Tomke Musa; Beat Keller; Susanne Vogelgsang (Food Additives & Contaminants: Part A, 2016)

Evolution and function of eukaryotic‐like proteins from sponge symbionts - David Reynolds; Torsten Thomas (Molecular Ecology, 2016)
Sponges (Porifera) are ancient metazoans that harbour diverse microorganisms, whose symbiotic interactions are essential for the host's health and function. Although symbiosis between bacteria and sponges are ubiquitous, the molecular mechanisms that control these associations are largely unknown. Recent (meta‐) genomic analyses discovered an abundance of genes encoding for eukaryotic‐like proteins ( ELP s) in bacterial symbionts from different sponge species. ELP s belonging to the ankyrin repeat ( AR ) class from a bacterial symbiont of the sponge Cymbastela concentrica were subsequently found to modulate amoebal phagocytosis. This might be a molecular mechanism, by which symbionts can control their interaction with the sponge. In this study, we investigated the evolution and function of ELP s from other classes and from symbionts found in other sponges to better understand the importance of ELP s for bacteria–eukaryote interactions. Phylogenetic analyses showed that all of the nine ELP s investigated were most closely related to proteins found either in eukaryotes or in bacteria that can live in association with eukaryotes. ELP s were then recombinantly expressed in Escherichia coli and exposed to the amoeba Acanthamoeba castellanii , which is functionally analogous to phagocytic cells in sponges. Phagocytosis assays with E. coli containing three ELP classes ( AR , TPR ‐ SEL 1 and NHL ) showed a significantly higher percentage of amoeba containing bacteria and average number of intracellular bacteria per amoeba when compared to negative controls. The result that various classes of ELP s found in symbionts of different sponges can modulate phagocytosis indicates that they have a broader function in mediating bacteria–sponge interactions.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Effect of interspecific competition on trait variation in P haeobacter inhibens biofilms - Carla Lutz; Torsten Thomas; Peter Steinberg; Staffan Kjelleberg; Suhelen Egan (Environmental Microbiology, 2016)
Summary Interspecific competition between bacteria shapes community dynamics, causing evolutionary changes that affect life history traits. Here, we studied the role of interspecific competition on the generation of trait diversity using a two‐species model system of marine, surface‐associated bacteria. Bacterial biofilms of Phaeobacter inhibens were established alone or in competition with Pseudoalteromonas tunicata and phenotypic traits of dispersal cells were assessed during biofilm development. P. inhibens dispersal isolates from competition biofilms displayed less phenotypic variation, were superior competitors, were less susceptible to predation, and reached higher planktonic biomass than isolates from noncompetition biofilms. Moreover, the maintenance of competitive ability exhibited by individual dispersal isolates from competition biofilms did not result in an obvious reduction (measured as a negative trait correlation) in other traits, but was rather positively correlated with planktonic growth. However, where negative correlations between traits were found, they were exhibited by individuals derived from noncompetitive biofilms, whose populations also had a higher degree of trait variation than those from biofilms experiencing competition. Our observations indicate that interspecific competition during biofilm formation is important for maintaining both competitive ability and affects variation in ecologically relevant traits. Given that most bacteria in biofilms exist in diverse, multispecies communities, an understanding of how bacteria respond to biotic factors such as interspecific competition is critical for understanding the dynamics of bacterial populations in both ecological and evolutionary time.

Effects of Feed Species and HUFA Composition on Survival and Growth of the Longsnout Seahorse (Hippocampus reidi) - Patrick Schubert; Lena Vogt; Klaus Eder; Torsten Hauffe; Thomas Wilke (Frontiers in Marine Science, 2016)

Interdisciplinary studies on the technical and economic feasibility of deep underground coal gasification with CO2 storage in bulgaria - Yong Sheng; Aleksey Benderev; Donka Bukolska; Kenneth Imo-Imo Eshiet; Carlos Dinis da Gama; Torsten Gorka; Michael Green; Nikolay Hristov; Ismini Katsimpardi; Thomas Kempka; Jordan Kortenski; Nikolaos Koukouzas; et al. (Mitigation and Adaptation Strategies for Global Change, 2016)

Unsaturated compounds induce up-regulation of CD86 on dendritic cells in the in vitro sensitization assay LCSA - Thomas Armin Frohwein; Anna Sonnenburg; Torsten Zuberbier; Ralf Stahlmann; Maximilian Schreiner (Archives of Toxicology, 2016)

Next-generation sequencing reveals differentially amplified tandem repeats as a major genome component of Northern Europe’s oldest Camellia japonica - Tony Heitkam; Stefan Petrasch; Falk Zakrzewski; Anja Kögler; Torsten Wenke; Stefan Wanke; Thomas Schmidt (Chromosome Research, 2015)

Continental‐scale variation in seaweed host‐associated bacterial communities is a function of host condition, not geography - Ezequiel M. Marzinelli; Alexandra H. Campbell; Enrique Zozaya Valdes; Adriana Vergés; Shaun Nielsen; Thomas Wernberg; Thibaut de Bettignies; Scott Bennett; J. Gregory Caporaso; Torsten Thomas; Peter D. Steinberg (Environmental Microbiology, 2015)
Summary Interactions between hosts and associated microbial communities can fundamentally shape the development and ecology of ‘holobionts’, from humans to marine habitat‐forming organisms such as seaweeds. In marine systems, planktonic microbial community structure is mainly driven by geography and related environmental factors, but the large‐scale drivers of host‐associated microbial communities are largely unknown. Using 16S‐r RNA gene sequencing, we characterized 260 seaweed‐associated bacterial and archaeal communities on the kelp E cklonia radiata from three biogeographical provinces spanning 10° of latitude and 35° of longitude across the Australian continent. These phylogenetically and taxonomically diverse communities were more strongly and consistently associated with host condition than geographical location or environmental variables, and a ‘core’ microbial community characteristic of healthy kelps appears to be lost when hosts become stressed. Microbial communities on stressed individuals were more similar to each other among locations than those on healthy hosts. In contrast to biogeographical patterns of planktonic marine microbial communities, host traits emerge as critical determinants of associated microbial community structure of these holobionts, even at a continental scale.

Multi-scale processes drive benthic community structure in upwelling-affected coral reefs - Corvin Eidens; Torsten Hauffe; Elisa Bayraktarov; Christian Wild; Thomas Wilke (Frontiers in Marine Science, 2015)

Hydrological variations on the Central Tibetan Plateau since the Last Glacial Maximum and their teleconnection to inter‐regional and hemispheric climate variations - THOMAS KASPER; TORSTEN HABERZETTL; JUNBO WANG; GERHARD DAUT; STEFAN DOBERSCHÜtz; LIPING ZHU; ROLAND MÄUSBACHER (Journal of Quaternary Science, 2015)
Decadal to sub‐decadal variability of inflow, evaporation and biological productivity derived from Lake Nam Co was used to reconstruct hydrological changes for the past ca. 24 k cal a BP. The timing of these variations corresponds to known climatic shifts on the Northern Hemisphere. After a dry and cold Last Glacial Maximum the lake level of Nam Co initially rose at ca. 20 k cal a BP. Moist but further cold conditions between ca. 16.2 and 14 k cal a BP correspond to Heinrich Event 1. A warm and moist phase between ca. 14 and 13 k cal a BP is expressed as a massive enhancement in inflow and biological productivity and might be associated with a first intensification of the Indian Ocean Summer Monsoon coinciding with the Bølling–Allerød complex. A two‐step decrease in inflow and a contemporaneous decline in biological productivity until ca. 11.8 k cal a BP points to cool and dry conditions during the Younger Dryas. Lake levels peak at ca. 9.4 k cal a BP, although hydrological conditions remain relatively stable during the Holocene with only low‐amplitude variations observed.

Invaders versus endemics: alien gastropod species in ancient Lake Ohrid - Christian Albrecht; Kirstin Föller; Catharina Clewing; Torsten Hauffe; Thomas Wilke (Hydrobiologia, 2014)

Prostaglandin E2 does not attenuate adrenergic-induced cardiac contractile response - Simon Pecha; Eileen Mudersbach; Klaus-Dieter Söhren; Samer Hakmi; Hermann Reichenspurner; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Bacterial pathogens, virulence mechanism and host defence in marine macroalgae - Suhelen Egan; Neil Daniel Fernandes; Vipra Kumar; Melissa Gardiner; Torsten Thomas (Environmental Microbiology, 2014)
Summary Macroalgae are important ecosystem engineers in temperate marine waters. The function of macroalgae is intimately linked to the composition and structure of their epibiotic bacterial, communities, and evidence has emerged that bacteria can also have a negative impact on their host by causing disease. A few examples exist where bacteria have been unambiguously linked to macroalgal disease, however in many cases, pathogenicity has not been clearly separated from saprophytic behaviour or secondary colonization after disease initiation. Nevertheless, pathogenic pressure by bacteria might be substantial, as macroalgae have evolved a range of innate and induced defence mechanism that have the potential to control bacterial attacks. The presence and abundance of virulence factors in marine bacteria, which have not previously been recognized as pathogens, also represents an underappreciated, opportunistic potential for disease. Given that virulence expression in opportunistic pathogens is often dependent on environmental conditions, we predict that current and future anthropogenic changes in the marine environment will lead to an increase in the occurrence of macroalgal disease. This review highlights important areas of research that require future attention to understand the link between environmental change, opportunistic pathogens and macroalgal health in the world's oceans.

Ankyrin‐repeat proteins from sponge symbionts modulate amoebal phagocytosis - Mary T. H. D. Nguyen; Michael Liu; Torsten Thomas (Molecular Ecology, 2014)
Bacteria–eukaryote symbiosis occurs in all stages of evolution, from simple amoebae to mammals, and from facultative to obligate associations. Sponges are ancient metazoans that form intimate symbiotic interactions with complex communities of bacteria. The basic nutritional requirements of the sponge are in part satisfied by the phagocytosis of bacterial food particles from the surrounding water. How bacterial symbionts, which are permanently associated with the sponge, survive in the presence of phagocytic cells is largely unknown. Here, we present the discovery of a genomic fragment from an uncultured gamma‐proteobacterial sponge symbiont that encodes for four proteins, whose closest known relatives are found in a sponge genome. Through recombinant approaches, we show that these four eukaryotic‐like, ankyrin‐repeat proteins ( ARP ) when expressed in E schericha coli can modulate phagocytosis of amoebal cells and lead to accumulation of bacteria in the phagosome. Mechanistically, two ARP s appear to interfere with phagosome development in a similar way to reduced vacuole acidification, by blocking the fusion of the early phagosome with the lysosome and its digestive enzymes. Our results show that ARP from sponge symbionts can function to interfere with phagocytosis, and we postulate that this might be one mechanism by which symbionts can escape digestion in a sponge host.

Monsoonal forcing of Holocene paleoenvironmental change on the central Tibetan Plateau inferred using a sediment record from Lake Nam Co (Xizang, China) - Stefan Doberschütz; Peter Frenzel; Torsten Haberzettl; Thomas Kasper; Junbo Wang; Liping Zhu; Gerhard Daut; Antje Schwalb; Roland Mäusbacher (Journal of Paleolimnology, 2014)

Procedural descriptions for analyzing digitized artifacts - Torsten Ullrich; Christoph Schinko; Thomas Schiffer; Dieter W. Fellner (Applied Geomatics, 2013)

Wasserbauliches und städtebauliches Modell als Grundlage der Umgestaltung der Sieg in der Siegener Innenstadt - Torsten Frank; Jens Bender; Jörg Wieland; Jürgen Jensen; Thomas Griese (WASSERWIRTSCHAFT, 2013)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

A new approach for dating introduction events of the quagga mussel (Dreissena rostriformis bugensis) - Katharina C. M. Heiler; Sascha Brandt; Christian Albrecht; Torsten Hauffe; Thomas Wilke (Biological Invasions, 2012)

Development and application of SINE-based markers for genotyping of potato varieties - Kathrin M. Seibt; Torsten Wenke; Cora Wollrab; Holger Junghans; Katja Muders; Klaus J. Dehmer; Kerstin Diekmann; Thomas Schmidt (Theoretical and Applied Genetics, 2012)

The role of barriers and gradients in differentiation processes of pyrgulinid microgastropods of Lake Ohrid - Kirstin Schreiber; Torsten Hauffe; Christian Albrecht; Thomas Wilke (Hydrobiologia, 2012)

Mollusc biodiversity in a European ancient lake system: lakes Prespa and Mikri Prespa in the Balkans - Christian Albrecht; Torsten Hauffe; Kirstin Schreiber; Thomas Wilke (Hydrobiologia, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Absorption and mobility of foliar-applied boron in soybean as affected by plant boron status and application as a polyol complex - Silke Will; Thomas Eichert; Victoria Fernández; Jens Möhring; Torsten Müller; Volker Römheld (Plant and Soil, 2011)

Improved estimates of mean sea level changes in the German Bight over the last 166 years - Thomas Wahl; Jürgen Jensen; Torsten Frank; Ivan David Haigh (Ocean Dynamics, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs were determined by geological processes and climate change in the Late Cenozoic - Çiğdem Akın; C. Can Bilgin; Peter Beerli; Rob Westaway; Torsten Ohst; Spartak N. Litvinchuk; Thomas Uzzell; Metin Bilgin; Hansjürg Hotz; Gaston‐Denis Guex; Jörg Plötner (Journal of Biogeography, 2010)
Aim Our aims were to assess the phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs and to estimate divergence times using different geological scenarios. We relate divergence times to past geological events and discuss the relevance of our data for the systematics of eastern Mediterranean water frogs. Location The eastern Mediterranean region. Methods Genetic diversity and divergence were calculated using sequences of two protein‐coding mitochondrial (mt) genes: ND2 (1038 bp, 119 sequences) and ND3 (340 bp, 612 sequences). Divergence times were estimated in a Bayesian framework under four geological scenarios representing alternative possible geological histories for the eastern Mediterranean. We then compared the different scenarios using Bayes factors and additional geological data. Results The extensive genetic diversity in mtDNA divides eastern Mediterranean water frogs into six main haplogroups (MHGs). Three MHGs were identified on the Anatolian mainland; the most widespread MHG with the highest diversity is distributed from western Anatolia to the northern shore of the Caspian Sea, and includes the type locality of Pelophylax ridibundus . The other two Anatolian MHGs are restricted to south‐eastern Turkey, occupying localities west and east of the Amanos mountain range. One of the remaining three MHGs is restricted to Cyprus; the second, to the Levant; and the third was found in the distribution area of European lake frogs ( P. ridibundus group), including the Balkans. Main conclusions Based on geological evidence and estimates of genetic divergence we hypothesize that the water frogs of Cyprus have been isolated from the Anatolian mainland populations since the end of the Messinian salinity crisis (MSC), that is, since c . 5.5–5.3 Ma, while our divergence time estimates indicate that the isolation of Crete from the mainland populations (Peloponnese, Anatolia) probably pre‐dates the MSC. The observed rates of divergence imply a time window of c. 1.6–1.1 million years for diversification of the largest Anatolian MHG; divergence between the two other Anatolian MHGs may have begun about 3.0 Ma, apparently as a result of the uplift of the Amanos Mountains. Our mtDNA data suggest that the Anatolian water frogs and frogs from Cyprus represent several undescribed species.

The Ty1-copia families SALIRE and Cotzilla populating the Beta vulgaris genome show remarkable differences in abundance, chromosomal distribution, and age - Beatrice Weber; Torsten Wenke; Ulrike Frömmel; Thomas Schmidt; Tony Heitkam (Chromosome Research, 2010)

An abundant and heavily truncated non-LTR retrotransposon (LINE) family in Beta vulgaris - Torsten Wenke; Daniela Holtgräwe; Axel V. Horn; Bernd Weisshaar; Thomas Schmidt (Plant Molecular Biology, 2009)

Continuous cultivation approach for fermentative succinic acid production from crude glycerol by Basfia succiniciproducens DD1 - Edzard Scholten; Torsten Renz; Jochen Thomas (Biotechnology Letters, 2009)

Transmural expression of ion channels and transporters in human nondiseased and end-stage failing hearts - Ewa Soltysinska; Søren-Peter Olesen; Torsten Christ; Erich Wettwer; Andras Varró; Morten Grunnet; Thomas Jespersen (Pflügers Archiv - European Journal of Physiology, 2009)

Stable isotope ecology of Miocene large mammals from Sandelzhausen, southern Germany - Thomas Tütken; Torsten Vennemann (PalZ, 2009)

A BAC library of Beta vulgaris L. for the targeted isolation of centromeric DNA and molecular cytogenetics of Beta species - Gunnar Jacobs; Daryna Dechyeva; Torsten Wenke; Beatrice Weber; Thomas Schmidt (Genetica, 2009)

Ein Atlas Content Management System für den neuen Statistischen Atlas der Schweiz - Thomas Schulz; Torsten Ullrich (KN - Journal of Cartography and Geographic Information, 2009)

Spatial smoothing techniques for the assessment of habitat suitability - Thomas Kneib; Jörg Müller; Torsten Hothorn (Environmental and Ecological Statistics, 2008)

Quetiapine in primary insomnia: a pilot study - Michael H. Wiegand; Florentina Landry; Torsten Brückner; Corina Pohl; Zdenko Veselý; Thomas Jahn (Psychopharmacology, 2008)

Structural and functional evolution of the P2Y12-like receptor group - Torsten Schöneberg; Thomas Hermsdorf; Eva Engemaier; Kathrin Engel; Ines Liebscher; Doreen Thor; Klaas Zierau; Holger Römpler; Angela Schulz (Purinergic Signalling, 2007)

The use of functional genomics for the identification of a gene cluster encoding for the biosynthesis of an antifungal tambjamine in the marine bacterium Pseudoalteromonas tunicata - Catherine Burke; Torsten Thomas; Suhelen Egan; Staffan Kjelleberg (Environmental Microbiology, 2007)
Summary A large insert library was created in Escherichia coli from the DNA of the surface‐associated marine bacterium Pseudoalteromonas tunicata. Screening of the library for antifungal activity resulted in the detection and identification of a large gene cluster encoding for the biosynthesis of an antifungal tambjamine. A biosynthetic pathway has been proposed based on analysis and annotation of the gene cluster.

Discharge and transport processes along the German Baltic Sea Coast - Herbert Siegel; Torsten Seifert; Gerald Schernewski; Monika Gerth; Thomas Ohde; Jan Reißmann; Victor Podsetchine (Ocean Dynamics, 2005)

Plasma concentration of intestinal- and liver-FABP in neonates suffering from necrotizing enterocolitis and in healthy preterm neonates - Florian Guthmann; Torsten Börchers; Christian Wolfrum; Thomas Wustrack; Sabine Bartholomäus; Friedrich Spener (Molecular and Cellular Biochemistry, 2002)

Cold stress response in Archaea - R. Cavicchioli; Torsten Thomas; Paul M. G. Curmi (Extremophiles, 2000)

Phylogenetic relationship and antifouling activity of bacterial epiphytes from the marine alga Ulva lactuca - Suhelen Egan; Torsten Thomas; Carola Holmström; Staffan Kjelleberg (Environmental Microbiology, 2000)
It is widely accepted that bacterial epiphytes can inhibit the colonization of surfaces by common fouling organisms. However, little information is available regarding the diversity and properties of these antifouling bacteria. This study assessed the antifouling traits of five epiphytes of the common green alga, Ulva lactuca . All isolates were capable of preventing the settlement of invertebrate larvae and germination of algal spores. Three of the isolates also inhibited the growth of a variety of bacteria and fungi. Their phylogenetic positions were determined by 16S ribosomal subunit DNA sequencing. All isolates showed a close affiliation with the genus Pseudoalteromonas and, in particular, with the species P. tunicata . Strains of this bacterial species also display a variety of antifouling activities, suggesting that antifouling ability may be an important trait for members of this genus to be highly successful colonizers of animate surfaces and for such species to protect their host against fouling.